SECOND TRIMESTER UTERINE RUPTURE WITH PLACENTA PERCRETA IN PREVIOUS LOWER SEGMENT CESAREAN SCAR - DUBBEWAR, AVINASH P; SRIVASTAVA, AJAI; SK, KATHPALIA; N HIREMATH, RAVISHEKAR; GHODKE, SANDHYA; CHOUREY, NIRAJ; SREENIVAS, AUDUKOORI (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Rupture of a pregnant uterus is a serious threat to the mother’s life and her unborn child. Most of the reported cases of uterine rupture in scarred uterus are due to dehiscence of previous cesarean scar or a rupture of myomectomy scar and usually occur in the third trimester. Spontaneous uterine rupture in first or second trimester is very rare. Here we report a case of second-trimester spontaneous uterine rupture with a particular emphasis on the etiological factors, discuss the course of events and difficulties in the diagnosis. The lesson learned from this case is that, although uterine rupture is very rare in the second trimester of pregnancy, it should be taken into consideration in the differential diagnosis of acute abdomen, especially if there is a predisposing factor such as previous lower segment caesarean section and fluid in the abdomen.